Pengaruh Intermitten Training terhadap Kapasitas Oksigen Maksimal Pemain Liga 1 Persela Lamongan FC - Ferizal, Moch. Sandy; Pamungkas, Hari; Kurniawan, Rubbi; Nidomuddin, Muhammad; Sudari, Sudari (MAN Insan Cendekia Jambi, 2024)
Aerobic endurance is an important element for a soccer player. Exercise brings changes and adaptations to the body, including increasing maximum oxygen capacity, including intermittent training. Football is a dynamic sport and is a big football sport that relies on excellent performance. The aim of this research is to test whether intermittent training has an effect on the maximum oxygen capacity of football players, namely Persela Lamongan FC players. The author uses experimental research. Intermittent training uses three posts (shuttle run, 2.4 km run, fartlek run) with a training frequency of 3 times a week face to face with progressive (gradual) intensity and load. The test instrument used by the author in this research is the Beep Test or MFT (Multi Fitness Stage). The significance value of the post-test results shows that there is an effect of intermittent training on the maximum oxygen capacity of Persela Lamongan FC players with >0.05 (sig=.076). The conclusion of this research is that there is an influence of intermittent training on the maximum oxygen capacity of Persela Lamongan players. The research results obtained show that the maximum oxygen capacity is in the Good category.